PART - WHOLE METHOD APPLICATION TO INCREASE TEAM COOPERATION AND SHORT SERVICE ABILITY - Rizka Yunita; Riyanto Riyanto; Turdjai Turdjai (DIADIK, 2018)
This study aims to determine the application of part-whole methods can improve team collaboration and short service skills of students in class VII.5 in SMP 14 Kota Bengkulu. The research used Kemmis Mc Taggrat's class action research. The subjects of this study were students of class VII.5 SMP 14 Kota Bengkulu. Data collection techniques used were test instruments and observation sheets. Data analysis techniques used t-test. The results of this study indicate that the application of the part-whole method can improve team collaboration and short service skills of students well. The implication in this study is using the part-whole method, students are better able to implement teamwork as a whole and are able to perform effective short services.